Rumen Bacteria Population of Bali Cattle Heifer Fed Rations Contain Different Energy and Protein Levels - K., Saragih; Suryani, N. N.; Lindawati, S. A. (Jurnal Peternakan Tropika, 2018)
This study aim to determine the total population of bacteria, cellulolytic bacteria, amylolytic bacteria and proteolytic bacteria in bali cattle heifers fed ration contain different energy and protein levels.  This study used rumen fluid taken from 12 balicattle heifers.  The study was conducted on February 22 nd – March 16 th 2018 in Livestock Product Technology and Microbiology Laboratory of Animal Husbandry Faculty, Udayana University.  This study used Randomized Block Design (RBD) with four treatments and three replications.  The treatments given is four types ration consist of 12% of crude protein and 2000 kcal ME / kg of energy (Treatment A), 13% of crude protein and 2100 kcal ME / kg of energy (Treatment B), 14% of crude protein and 2200 kcal ME / kg of energy (Treatment C) and 14% of crude protein and 2300 kcal ME / kg of energy (Treatment D).  Rumen fluid from bali cattle heifer obtained for rumen bacteriacalculation.Variables observed were total population of bacteria (colony/ml), cellulolytic bacteria (colony/ml), amylolytic bacteria (colony/ml) and proteolytic bacteria (colony/ml).  Data obtained was analyzed using variance analysis and if the results were affected significantly different (p <0.05) then the analysis was continued with Duncan distance test.  The result of variance analysis showed that treatments gave no significant affect (P> 0.05) of the total population of bacteria, cellulolytic bacteria, amylolytic bacteria and proteolytic bacteria.  The total population of bacteria, cellulolytic bacteria, amylolytic bacteria and proteolytic bacteria obtained were 1.1-5.7 × 10 9 cfu/ml of rumen fluid, 1.5-4.5 × 10 5 cfu/ml of  rumen fluid, 1.3-6.3 × 10 5 cfu/ml of rumen fluid and 2.7-8.3 × 10 7 cfu/ml of rumen fluid.  Based on the results of this study, it can be concluded that the given of 12% to 15% of crude protein content and energy 2000 kcal ME / kg to 2300 kcal ME / kg of energy content did not affect the total population of bacteria, cellulolytic bacteria, amylolytic bacteria and proteolytic bacteria in the bali cattle heifers' rument bacteria. Keywords : population of rumen bacteria, energy and protein levels, bali cattle heifer